2021
DOI: 10.2147/idr.s304569
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Chronic Lung Abscess Associated with Parvimonas micra Diagnosed Using Metagenomic Next-Generation Sequencing

Abstract: Parvimonas micra (P. micra) is a Gram-positive anaerobic bacterium distributed in the oral cavity, with a potential to become pathogenic causing lung abscess. Due to the lack of specificity of symptoms and the difficulty in culture, the diagnosis of lung abscess associated with P. micra is delayed. It is essential to elucidate the clinical characteristics of lung abscess associated with P. micra. Methods: From January 2019 to July 2020, five patients with chronic lung abscess associated with P. micra diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…Purulent diseases are typical pathologies of P. micra infection, and patients with lung abscess due to P. micra were reported in elderly men with poor oral hygiene who smoke and drink heavily. 1,2 However, the present patient had no such risk factors. The patient did not respond to the antibiotics given and only improved after the surgical intervention indicating the high virulence of this bacteria.…”
contrasting
confidence: 52%
“…Purulent diseases are typical pathologies of P. micra infection, and patients with lung abscess due to P. micra were reported in elderly men with poor oral hygiene who smoke and drink heavily. 1,2 However, the present patient had no such risk factors. The patient did not respond to the antibiotics given and only improved after the surgical intervention indicating the high virulence of this bacteria.…”
contrasting
confidence: 52%
“…It also affects oral microbiota composition ( 21 ). The level of P. micra and other bacteria in the oral cavity is higher in smokers than in non-smokers ( 8 ). We also noted poor hygiene with suspected periodontitis and decreased α diversity in the oral microbiome of our patient, accompanied by similar copies of P. micra between oral wash and BALF samples.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have suggested that the durations of antibiotic therapy for P. micra pneumonia are highly variable ( 8 ) and there is little evidence of hematogenous P. micra pneumonia. Watanabe et al ( 7 ) reported a case of P. micra -related hematogenous lung abscess in which chest CT showed that the lung lesions resolved after 1 month of antibiotic treatment with ampicillin sulbactam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the fast development of molecular biology, metagenomic next-generation sequence (mNGS),a novel and promising approach, has emerged as pan-pathogen assays for infectious diseases diagnosis, especially for the detection of atypical, rare, or slow-growing microbes [9][10][11].To date, many studies have addressed the value of mNGS in detected the causative pathogens and guided targeted antimicrobial therapy more quikly [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%